Tracheospasmolytic activity of vitetrifolin-E isolated from the leaves of Vitex trifolia L. - Alam, G.; Gandjar, I.G.; Hakim, Lukman; Timmerman, H.; Veerporte, R.; Wahyuono, S. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
In searching of tracheospasmolytic active compounds from Vitex trifolia, we are now reporting isolation and identification of vitetrifolin-E from active fraction obtained from n-hexane extract of V. trifolia. Vitetrifolin-E blocked spontaneous contraction of male guinea pig trachea induced by histamine and was active in a model using sensitized guinea pig trachea stimulated by ovalbumin. Vitetrifolin-E inhibited tracheal contraction by 22.6% at dose of 1.3 x 10-4 M and by 86.1% at dose of 4.10-4 M. In a model using sensitized male guinea pig trachea, vitetrifolin-E also inhibited the contraction 83.5% (1.3 x 10-5 M).Keywords: vitetrifolin-E, Vitex trifolia, tracheospasmolytic